(±)‐Asarinin. (4th January 2013) - Negi, Devendra Singh; Negi, Nisha; Kumar, Ashok; Matsunami, Katsuyoshi; Schulz, Stefan; Jones, Peter G.
<x xml:space="preserve">Abstract</x> Asarinin, C20H18O6, was isolated as a racemate from the shrub Zanthoxylum alatum. Both forms of the enantiomerically pure substance, (+)‐ and (−)‐asarinin, have been the subject of a total of five previous structure determinations that are essentially identical except for the absolute stereochemistry. However, there seems to be some confusion in the literature concerning these structure determinations of asarinin and also those of its stereoisomer sesamin. The molecular structure of racemic asarinin differs from that of the pure enantiomers in the orientation of one ring system. In the packing of the racemate, molecules are linked by C—H...O interactions to form ribbons parallel to [101].